Toxoplasma gondii stabilises tetrameric complexes of tyrosine‐phosphorylated signal transducer and activator of transcription‐1 and leads to its sustained and promiscuous DNA binding. (7th August 2018) - Nast, Roswitha; Staab, Julia; Meyer, Thomas; Lüder, Carsten G.K.
Abstract: Toxoplasma gondii is an obligate intracellular parasite that infects up to 30% of humans worldwide. It can lead to severe diseases particularly in individuals with immature or defective immune responses. Control of T. gondii relies on the IFN‐γ‐induced signal transducer and activator of transcription‐1 (STAT1) pathway. T. gondii, however, largely inactivates STAT1‐mediated gene transcription by T. gondii inhibitor of STAT1‐dependent transcription (TgIST), a parasite effector protein binding to STAT1. Here, we have analysed requirements of STAT1 to bind TgIST and characterised downstream effects on STAT1 signalling. TgIST bound to STAT1 dimers but more efficiently assembled with STAT1 tetramers, which are essential for effective IFN‐γ responsiveness. Such binding was abrogated in N‐terminal, but not C‐terminal deletion mutants of STAT1. Furthermore, TgIST did not bind to the STAT1 F77A substitution mutant that cannot form STAT1 tetramers, resulting in a complete unresponsiveness of parasite‐infected STAT1 F77A ‐expressing cells to IFN‐γ. Remarkably, binding of TgIST considerably increased the affinity of the aberrant STAT1 tetramers for DNA consensus sequence binding motifs and even enabled binding to nonconsensus sequences. Consistent with the increased DNA binding, STAT1 from parasite‐infected cells remained phosphorylated at Tyr 701 and Ser 727 and was retained within the nucleus in a DNA‐bound state. The sustained and promiscuous binding activity particularly of STAT1 tetramers to unspecific DNA sites lacking a consensus STAT1‐binding motif is an as yet unrecognised mechanism contributing to the defective IFN‐γ‐mediated signalling in T. gondii ‐infected cells.